Indonesian Modified Checklist for Autism in Toddler, Revised with Follow-Up (M-CHAT-R/F) for Autism Screening in Children at Sanglah General Hospital, Bali-Indonesia. - Windiani, I Gusti Trisna; Soetjiningsih, S.; Adnyana, I Gusti Agung Sugitha; Lestari, Kadek Apik (BALI MEDICAL JOURNAL, 2016)
Background: Autism Spectrum Disorder (ASD) is a developmental disorder characterized by impaired reciprocal social interaction and communication, and by a restricted, repetitive or stereotyped behavior. Early detection of autism is recommended on all toddlers from the ages of 9 months because of increasing in prevalence. The Modified Checklist for Autism (M-CHAT) in Toddlers, a Revised with Follow-Up (M-CHAT-R/F) is a 2-stage parent-report screening tool to assess a risk for ASD and it demonstrates an improvement compared to the original M-CHAT. It is translated to Indonesian language by Soetjiningsih and colleagues, and it needs to be validated. Methods: This is a diagnostic accuracy study conducted at Sanglah Hospital, Bali, conducted from March 2015 to December 2016. We included children 18-48 months in this study. The parents of the outpatient children in the growth and development clinic of Sanglah Hospital were asked to fill out the Indonesian M-CHAT-R/F form. In the same visit, the Autism Spectrum Disorder (ASD) assessment according to the DSM-5 as a gold standard was done by the researchers, without knowing the M-CHAT -R/F result. The assessment comparison based on M-CHAT-R/F and DSM-5 was analyzed to obtain the AUC intersection on ROC curve that gives the best sensitivity and specificity. Results: We found 10.71% of our outpatient was diagnosed with autism according to DSM 5, when they are 18-24 months old. The Indonesian version of M-CHAT-R/F as an ASD screening tool has 88.9% in sensitivity and 94.6% in specificity. Conclusion: Our results suggest that the Indonesian translation of the M-CHAT-R/F is an effective screening instrument for ASD, particularly when a two-step screening process is used.